2012
DOI: 10.4314/ajtcam.v9i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties and inhibitory effect of ethanolic extract of <i>Struchium sparganophora</i> (Ewuro odo) leaf on α - amylase and α – glucosidase activities

Abstract: Recent studies have shown that vegetables consumption could lower the risk of diabetes mellitus. Therefore, this study sought to investigate the inhibitory effect of Struchium sparganophora (Ewuro Odo) leaf on key enzyme linked to type-2 diabetes (α-amylase and α-glucosidase) as well as assessing the effect of blanching (a commonly practiced food processing technique) of this leafy vegetable on these key enzymes. Fresh leaves of Struchium sparganophora were blanched in hot water for 10 minutes, and the 70% eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Phenolics are compounds of one (or more) aromatic rings with one or more hydroxyl groups and are therefore potentially able to quench free radicals by forming resonance‐stabilized phenoxyl radicals (Oboh, Akinyemi, & Ademiluyi, ). This was demonstrated by the phenolic‐rich extracts of mistletoe from different host plants used in this study as they were able to prevent the production of Fe and SNP‐induced TBARS; a biomarker of lipid peroxidation and oxidative stress (Puntel, Nogueira, & Rocha, ).…”
Section: Discussionmentioning
confidence: 99%
“…Phenolics are compounds of one (or more) aromatic rings with one or more hydroxyl groups and are therefore potentially able to quench free radicals by forming resonance‐stabilized phenoxyl radicals (Oboh, Akinyemi, & Ademiluyi, ). This was demonstrated by the phenolic‐rich extracts of mistletoe from different host plants used in this study as they were able to prevent the production of Fe and SNP‐induced TBARS; a biomarker of lipid peroxidation and oxidative stress (Puntel, Nogueira, & Rocha, ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are also comparable to the previous studies about antidiabetic activities of different plant extracts. It was reported that Nepeta nuda subsp., Glandulifera, and N. Cadmea extracts (Sarikurkcu et al, 2019), jute leaf extract (Oboh et al, 2012), soybean extracts (Ademiluyi & Oboh, 2013) finger millet (Eleusine coracana L.) seed coat extracts (Shobana et al, 2009), Senecio biafrae leaves extract (Ajiboye et al, 2018), and pomegranate peel extract (Demir et al, 2019) could inhibit α-amylase and α-glucosidase in different degrees. Also, the studies about individual phenolic compounds reported that caffeic, coumaric acid (Pulbutr et al, 2017), gallic acid (Oboh et al, 2016), naringenin, kaempferol, luteolin, apigenin, catechin, epicatechin, daidzein, and epigallocatechin gallate (Tadera, Minami, Takamatsu, & Matsuoka, 2006) had inhibitory activities in different degrees against α-amylase and α-glucosidase.…”
Section: Antidiabetic Activity Of Cherry Stem Extractmentioning
confidence: 99%
“…Furthermore, they have many biological activities including antiallergen, antimutagenic, anticarcinogen, antiglycemic, anticholesterol, anti‐inflammatory, antimicrobial, and tranquilizing properties that could be used in cosmetic, drug, and food industries (Shahidi & Ambigaipalan, 2015). Therefore, the number of researches investing the biological effects of the plants have been increased for the last years (Ademović et al, 2017; Aires, Dias, Carvalho, & Saavedra, 2017; Ajiboye et al., 2018; Alaba & Chichioco‐Hernandez, 2014; Daniela et al, 2007; Demir, Akpınar, Kara, & Güngör, 2019; Nessa, Ismail, & Mohamed, 2010; Oboh, Akinyemi, & Ademiluyi, 2012; Oboh, Ogunsuyi, Ogunbadejo, & Adefegha, 2016; Pulbutr et al., 2017; Sarikurkcu, Eskici, Karanfil, & Tepe, 2019; Shobana, Sreerama, & Malleshi, 2009; Zhishen, Mengcheng, & Jianming, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenol‐rich extracts from C. olitorius and V. amygdalina exhibited marked inhibitory effects on key enzymes linked to type 2 diabetes ( α ‐amylase and α ‐glucosidase) and hypertension (angiotensin I converting enzyme), providing a possible mechanism for reducing the risk of type 2 diabetes and hypertension . Similarly, antioxidant properties and enzyme inhibition could be part of the mechanism by which T. occidentalis and S. sparganophora reduce blood sugar and the risk of type 2 diabetes . Other African traditional leafy vegetables that have exhibited significant (>70%) inhibition of α ‐amylase activity that could result in reduced blood glucose levels and reduced risk of diabetes include Centella asiatica , C. tribola , C. monophylla , A. hybridus , J. flava , C. album and P. oleracea .…”
Section: Functional Foodsmentioning
confidence: 99%